2019
DOI: 10.1038/s41380-019-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in the serotonin receptor 7 gene (HTR7), rs7905446, is associated with good response to SSRIs in bipolar and unipolar depression

Abstract: Predicting antidepressant response has been a clinical challenge for mood disorder. Although several genome-wide association studies have suggested a number of genetic variants to be associated with antidepressant response, the sample sizes are small and results are difficult to replicate. Previous animal studies have shown that knockout of the serotonin receptor 7 gene (HTR7) resulted in an antidepressant-like phenotype, suggesting it was important to antidepressant action. In this report, in the first stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Likewise, a very recent work showed that one single nucleotide polymorphism located in the promoter region of the 5-HT7R gene is associated with a better response to two antidepressants, paroxetine and fluoxetine, that are selective 5-HT reuptake inhibitors. These data provide novel pharmacogenomic evidence to support the role of 5-HT7R in antidepressant response [86].…”
Section: The 5-ht7r and Neurological Diseasesmentioning
confidence: 68%
“…Likewise, a very recent work showed that one single nucleotide polymorphism located in the promoter region of the 5-HT7R gene is associated with a better response to two antidepressants, paroxetine and fluoxetine, that are selective 5-HT reuptake inhibitors. These data provide novel pharmacogenomic evidence to support the role of 5-HT7R in antidepressant response [86].…”
Section: The 5-ht7r and Neurological Diseasesmentioning
confidence: 68%
“…Likewise, a very recent work showed that one single nucleotide polymorphisms located in the promoter region of the 5-HT7R gene is associated with better response to two antidepressants, paroxetine and fluoxetine, that are selective 5-HT reuptake inhibitors. These data provide novel pharmacogenomic evidence to support the role of 5-HT7R in antidepressant response [83]. However, pharmacological and genetic manipulation of 5-HT7R in animal models of depression, anxiety and schizophrenia has often given inconsistent or conflicting results.…”
Section: The 5-ht7r and Neurological Diseasesmentioning
confidence: 89%
“…Furthermore, a variant of 5-HTR7 has been associated to a better response to SSRIs in bipolar patients [29].…”
Section: One Of the Most Remarkable And Clinically Relevant Examples mentioning
confidence: 99%
“…Moreover, 5-HTR7 has been implicated in mood control, based on pharmacological studies showing that antagonizing 5-HTR7 attenuates anxiety and depression-like phenotypes [ 25 28 ]. Furthermore, a variant of 5-HTR7 has been associated to a better response to SSRIs in bipolar patients [ 29 ].…”
Section: Introductionmentioning
confidence: 99%